Menjelajahi Fenomena Sosial Dalam Pendididkan dan Teologi: Tantangan dan Peluang - Sutarman Laia; Putri Sory; Sandra R Tapilaha (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Social phenomena and contextual issues in education and theology will discuss various contemporary social phenomena that influence the education and theology system, giving rise to contextual issues that arise in current educational and theological practices, the impact of social phenomena and contextual issues in education and theology on the development of society and religion. As well as things that can respond effectively to existing social challenges and contextual issues. In compiling this article, the author used descriptive qualitative methods. The descriptive qualitative method is a research method that creates systematic, factual and accurate descriptions (words) and images regarding the facts being investigated. The author looks for supporting facts through previous research from journals or books in accordance with the problems raised based on the findings. findings, facts and literature that support finding solutions to existing problems. This concerns cultural and religious diversity, issues of morality in the digital era. And not only that, the impact of social phenomena and contextual issues will be discussed, including the contextual meaning and purpose of education and theology, the context that shapes educational and theological theories, how do we do education and theology in a context like this? That is, being a witness to society , building dialogue between religious communities, creating harmony. The social phenomena and contextual issues in education and theology are such that the challenges in these two fields are often interrelated. Education must be responsive to social change and consider contextual issues, while theology also needs to understand social dynamics to provide views that are relevant in the context of life. The synergy between education and theology can help shape a more inclusive society and a deeper understanding of human values.